Fatigue and Muscle Atrophy in a Mouse Model of Myasthenia Gravis Is Paralleled by Loss of Sarcolemmal nNOS - Meinen, Sarina; Lin, Shuo; Rüegg, Markus A.; Punga, Anna Rostedt (PLOS ONE, 2012)
Myasthenia Gravis (MG) patients suffer from chronic fatigue of skeletal muscles, even after initiation of proper immunosuppressive medication. Since the localization of neuronal nitric oxide synthase (nNOS) at the muscle membrane is important for sustained muscle contraction, we here study the localization of nNOS in muscles from mice with acetylcholine receptor antibody seropositive (AChR+) experimental autoimmune MG (EAMG). EAMG was induced in 8 week-old male mice by immunization with AChRs purified from torpedo californica. Sham-injected wild type mice and mdx mice, a model for Duchenne muscular dystrophy, were used for comparison. At EAMG disease grade 3 (severe myasthenic weakness), the triceps, sternomastoid and masseter muscles were collected for analysis. Unlike in mdx muscles, total nNOS expression as well as the presence of its binding partner syntrophin α-1, were not altered in EAMG. Immunohistological and biochemical analysis showed that nNOS was lost from the muscle membrane and accumulated in the cytosol, which is likely the consequence of blocked neuromuscular transmission. Atrophy of all examined EAMG muscles were supported by up-regulated transcript levels of the atrogenes atrogin-1 and MuRF1, as well as MuRF1 protein, in combination with reduced muscle fiber diameters. We propose that loss of sarcolemmal nNOS provides an additional mechanism for the chronic muscle fatigue and secondary muscle atrophy in EAMG and MG.